Video media as a learning aid for dance: A needs analysis study in junior high school - Burga, Nurhinayah; Hasyim, Nurhikmah; Muin, Awaluddin; Hardianto, Hardianto; Burga, Muhammad Alqadri (Journal of Research in Instructional, 2025)
Dance learning in junior high schools in Indonesia faces various challenges, especially related to the limitations of learning media and existing facilities. One of the solutions that is developing is the use of video media to demonstrate dance movements more effectively. This study aims to identify the needs of dance demonstration video media needed by teachers and students at Junior High School 2 Liliriaja, Soppeng, Indonesia. The research method used is qualitative descriptive with thematic analysis. Data was collected through an open questionnaire filled out by teachers and 30 students, which were then analyzed to identify themes related to the use of video media in dance learning. The results showed that teachers and students wanted video media that displayed clear dance movement steps, accompanied by music, and contained elements such as school profiles and student achievement. Teachers also hope that there are adequate facilities and infrastructure to support the use of online-based video media. In conclusion, dance demonstration video media is needed by teachers and students in cultural arts learning so that it can improve the quality of dance art learning in schools, and allow students to learn independently and flexibly. Future research recommendations are the need to develop dance demonstration videos that are valid, practical, and effective in learning cultural arts in junior high school.